1998
DOI: 10.1002/he.10105
|View full text |Cite
|
Sign up to set email alerts
|

Beginning Graduate School: Explaining First‐Year Doctoral Attrition

Abstract: A graduate student's decision not to continue in an initial program is that student's answer to one or more questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
329
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(350 citation statements)
references
References 3 publications
14
329
2
5
Order By: Relevance
“…It is a process not only focused on developing the practice of research, but also the development of an identity within a particular field (Golde, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a process not only focused on developing the practice of research, but also the development of an identity within a particular field (Golde, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance isolation (Gardner & Holley, 2011), stress due to lack of adequate tutor support (Golde, 1998;Seagram, Gould, & Pyke, 1998), cultural barriers (McAlpine, Paulson, Gonsalves, & Jazvac-Martek, 2012), financial issues (Moyer & Salovey, 1999), struggles due to family lives (Offerman, 2011), lack of adequate balancing of family and worklife (Brus, 2006) have been identified as challenges in literature. In addition, challenges arise because of lack of adequate social support from family members or fellow peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perhaps half of all doctoral students do not complete their studies (Lovitts, 2001) and some of these are likely to produce publications before switching to a different career. Failure to complete a doctorate is not necessarily a career failure because the student may leave after realising that a PhD will not help them to get the job that they want (Golde, 1998). A survey of US doctorate recipients in 2000 found that just over half of those that were US citizens intended to work in higher education (Hoffer, Dugoni, Sanderson, Sederstrom, Ghadialy, & Rocque, 2001).…”
Section: Productivity and Careersmentioning
confidence: 99%